Concertino para Contrabaixo e Orquestra de Câmara de José Siqueira: um processo de edição, análise e redução para piano e contrabaixo - Andrade, Danilo Cardoso de (2011)
This work intends to contribute to the appreciation of the Brazilian music for double bass, more precisely the Concertino para Contrabaixo e Orquestra de Câmara by the composer José Siqueira. It consists of a set of studies to serve as a tool for the construction for the performance of this work. It‟s organized in three chapters. The first is a historical report about the composer's career and his compositional systems. The second chapter covers the contextualization of the concertino, revising, editing and finally a reduction for piano and double bass piano. The third is an analysis of the work addressing thematic and structural aspects as a way to help to perform it.